The Misadventures of Salem Hyde - 1 1, Spelling trouble - Cammuso, Frank (New York Amulet Books, 2013)
Frequently admonished for her impulsive behavior, Salem Hyde, a young witch, ignores long lectures by her dignified animal companion and enters a spelling competition at school only to discover that the "spelling" involves words instead of magic.
Keywords: Witches -- Comic books, strips, etc; Magic -- Comic books, strips, etc; Spelling bees -- Comic books, strips, etc; Schools -- Comic books, strips, etc; Graphic novels; Witches -- Fiction; Magic -- Fiction; Spelling bees -- Fiction; Schools -- Fiction; Graphic novels; Fantasy comic books, strips, etc; Graphic novels; Comic books, strips, etc